2020
DOI: 10.1590/0103-6440202003120
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Affects Proliferation, Reactive Oxygen Species and Mineralization of Human Dental Pulp Cells

Abstract: Diabetes is a group of metabolic disorders that can lead to damage and dysfunction of many organs including the dental pulp. Increased inflammatory response, reduction of dentin formation and impaired healing were reported in diabetic dental pulp. Hyperglycemia, which is a main characteristic of diabetes, was suggested to play a role in many diabetic complications. Therefore our aim was to investigate the effects of high glucose levels on proliferation, reactive oxygen species (ROS) production and odontogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It demonstrated that the induced periapical lesions were significantly larger with severe alveolar bone resorption and more bacteria in the diabetic rat's model than in non‐diabetic controls (Fouad et al, 2002; Iwama et al, 2003; Kohsaka, 1996; Samuel et al, 2019). This suggests that the hyperglycaemic environment, impaired immune response and dental pulp circulatory disorders resulted in decreased oxygen supply that favours microorganism proliferation and promotes colonization, especially the growth of anaerobic organisms in diabetic patients (Bender & Bender, 2003; Horsophonphong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated that the induced periapical lesions were significantly larger with severe alveolar bone resorption and more bacteria in the diabetic rat's model than in non‐diabetic controls (Fouad et al, 2002; Iwama et al, 2003; Kohsaka, 1996; Samuel et al, 2019). This suggests that the hyperglycaemic environment, impaired immune response and dental pulp circulatory disorders resulted in decreased oxygen supply that favours microorganism proliferation and promotes colonization, especially the growth of anaerobic organisms in diabetic patients (Bender & Bender, 2003; Horsophonphong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that elevated AGE levels might promote pulp calcification in diabetic rats [126]. In contrast, high glucose levels inhibited the proliferation of human dental pulp cells and their odontogenic differentiation, as well as stimulated ROS production [127]. Therefore, hyperglycaemia plays a negative role in the healing and regeneration of pulp and periapical tissues in patients with diabetes.…”
Section: The Diabetes-induced Consequences For the Cellular Metabolis...mentioning
confidence: 98%
“…Based on an in vitro study, Horsophonphong et al [127] found that high glucose levels decreased the proliferation and odontogenic differentiation of human dental pulp cells. Additionally, a high glucose level induced ROS production and reduced glutathione (GSH) level, suggesting an imbalance between free radical synthesis and antioxidant defence that may cause cellular damage.…”
Section: The Diabetes-induced Consequences For the Cellular Metabolis...mentioning
confidence: 99%
“…Cell treatment with ethanolic extract of P. ostreatus caused a slight but significant increase in reduced RGR (Figure 2B). High and low glucose conditions markedly affect the proliferation of most cells (Horsophonphong et al, 2020;Pluskal et al, 2011) due to variable glucosemediated responses including alterations in gene expression, metabolic processes, or antioxidant status of the cell. This suggests that the positive effect of P. ostreatus extract on cell proliferation results from its collateral impact on the regulation of different essential cellular processes.…”
Section: Growth Of Cells Under Hypo-and Hyper-glycemic Stressmentioning
confidence: 99%